PAR-Complex and Crumbs Function During Photoreceptor Morphogenesis and Retinal Degeneration - Pichaud, Franck (Frontiers in Cellular Neuroscience, 2018)
The fly photoreceptor has long been used as a model to study sensory neuron morphogenesis and retinal degeneration. In particular, elucidating how these cells are built continues to help further our understanding of the mechanisms of polarized cell morphogenesis, intracellular trafficking and the causes of human retinal pathologies. The conserved PAR complex, which in flies consists of Cdc42-PAR6-aPKC-Bazooka, and the transmembrane protein Crumbs (Crb) are key players during photoreceptor morphogenesis. While the PAR complex regulates polarity in many cell types, Crb function in polarity is relatively specific to epithelial cells. Together Cdc42-PAR6-aPKC-Bazooka and Crb orchestrate the differentiation of the photoreceptor apical membrane and zonula adherens, thus allowing these cells to assemble into a neuro-epithelial lattice. In addition to its function in epithelial polarity, Crb has also been shown to protect fly photoreceptors from light-induced degeneration, a process linked to Rhodopsin expression and trafficking. Remarkably, mutations in the human Crumbs1 (CRB1) gene lead to retinal degeneration, making the fly photoreceptor a powerful disease model system.